A Terrific New World: Polar Space in the Narrative, Journals and Letters of John Franklin’s First Arctic Expedition (1819-22) - Nicoletta BRAZZELLI (E-REA)
Franklin’s first exploration of the Northern coast of Canada captured the public imagination thanks to his Narrative of a Journey to the Shores of the Polar Sea in the Years 1819-22, published in 1823, which conveys the drama of an expedition plagued by harsh weather, bad planning, starvation and even murder. Franklin’s journals and letters written during the expedition, by focusing on planning details and material conditions of travel itself throw fresh light on his much debated mission. Franklin’s texts reveal thus varying perspectives on the events according to the audiences being addressed and the author’s perception of these reading publics.